2018
DOI: 10.1097/mej.0000000000000441
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of infrared thermography in an emergency department

Abstract: ΔN and ΔF showed a significant association with 30-day mortality, suggesting a prognostic value. However, this was a small pilot study with few events. Larger studies are warranted for confirmation of these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 12 publications
1
14
0
Order By: Relevance
“…Thermography has been used very rarely in clinical medicine; the technique is primarily used in the industrial sector [3] . However, thermography is extremely accurate at identifying differences in surface temperature and can therefore show increases in skin temperature, as in this case [4] . Since necrotizing fasciitis is a challenging diagnosis to make and clinical observation is very difficult, we believe thermographic imaging could contribute significantly to making this diagnosis in the ED.…”
Section: Discussionmentioning
confidence: 99%
“…Thermography has been used very rarely in clinical medicine; the technique is primarily used in the industrial sector [3] . However, thermography is extremely accurate at identifying differences in surface temperature and can therefore show increases in skin temperature, as in this case [4] . Since necrotizing fasciitis is a challenging diagnosis to make and clinical observation is very difficult, we believe thermographic imaging could contribute significantly to making this diagnosis in the ED.…”
Section: Discussionmentioning
confidence: 99%
“…In a small pilot study, Holm et al showed an association between short-term mortality and the gradient between core temperature (measured in the inner canthus of the eye) and the peripheral temperature (measured at the tip of the nose). 5 These findings suggest that the gradient between core and peripheral temperature could be an early marker of clinical deterioration. This study was designed to validate these findings in a larger two-center cohort of acutely admitted medical patients, by examining the association between this core-peripheral temperature gradient and 30-day Thermographic visualization of facial vasoconstriction is associated with 30-day all-cause mortality in medical patients; prospective observational two-site cohort study Key Points…”
Section: Introductionmentioning
confidence: 93%
“…Four points from each patient's image were noted; inner canthus of the eye (core point) and nose tip, earlobe, and fingertip of the middle finger (peripheral points). The main analysis, based on the prior study by Holm et al, 5 was on the core to nose temperature gradient. The gradients between core and finger and core and ear were considered secondary analyses.…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such an improvement may be provided by a measurement strategy that involves different sites (Kessel et al 2010;Fernandes et al 2016;Teunissen & Daanen, 2011), several sites (Holm et al 2018, Niedermann et al 2014, the differential between different sites, or a combination of measured variables (Sun et al 2017, Richmond et al 2015. Any method for mass screening must consider that in clothed individuals only certain surface areas of the skin will be exposed, and that predictions of T core will be limited by scanning only these regions.…”
Section: Possible Solutions?mentioning
confidence: 99%